TEACHER AND SCHOOL RESPONSES TO ANTI-BULLYING POLICIES AND RELIGIOUS MINORITY STUDENTS IN INDONESIA - Susanti, Rela; Rachmawati , Tutik (Universitas Kristen Satya Wacana, 2025)
ABSTRACT Bullying remains prevalent because many teachers and schools have not fully adopted perspectives of tolerance and diversity. This lack of approach is a major factor in the high incidence of bullying against religious minority students in Indonesia. In this context, it is important to understand how anti-bullying policies are implemented in schools, particularly in relation to the treatment of students from religious minority groups. The purpose of this study is to conduct an in-depth analysis of how schools and teachers in Indonesia respond to existing anti-bullying regulations, with a specific focus on how they treat children from religious minority groups. This study employs a qualitative approach with in-depth interview methods to explore the responses and experiences of teachers, schools, and students themselves. By deeply analyzing the responses from educators and schools, as well as the experiences of students, this study aims to identify gaps in policy implementation and provide methods to enhance the effectiveness of anti-bullying measures. The potential impact of this research is to ensure that religious minority children are provided with an environment that supports their identities, so they can feel safe and valued in their educational environment. Additionally, this research is expected to serve as a foundation for formulating more inclusive and effective policies in preventing bullying in the future.